Learning Method of Al-Qur’an Hadith at The Islamic Junior Hight School Level in The Independent Curriculum - Firdaus, Firdaus; Aguswan, Aguswan; AM, Rusydi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
Learning A1-Qur’an Hadith in Islamic junior high schools faces various challenges in efforts to instill Islamic values in the digital era and the implementation of the Independent Curriculum. This research aims to examine the application of innovative methods, such as integrative thematic approaches, collaborative learning, project-based learning, and the use of digital technology in improving student understanding. With the method used which is qualitative-descriptive with literature study and semi-structured interviews, the results of the study show that innovative learning methods not only improve students’ understanding of Islamic values, but also develop 21st century skills, such as critical thinking, creativity, and collaboration. However, its implementation faces obstacles in the form of limited facilities, lack of teacher competence, and resistance to change. Therefore, a strategy is needed that includes teacher training, adequate technology procurement, and synergy between schools, governments, and communities.